2018
DOI: 10.1055/a-0631-8813
|View full text |Cite
|
Sign up to set email alerts
|

Snacking is Common in People with Diabetes Type 1 and Type 2 with Insulin Therapy and Is Not Associated With Metabolic Control or Quality of Life

Abstract: Snacking seems to be a common habit in individuals with diabetes and most of them like to snack. Snacking is not associated with better or worse metabolic control or quality of life. The decision to snack or not to snack can be left to the individual and integrated into the therapy without danger for the glycaemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition to commonly used mid-meal snacks ( 13 , 42 ), pre-load represents a novel dietary approach to lower post-prandial glycemic excursions ( 14 , 43 ). A variety of foods, such as olive oil, milk proteins, fruits, and low-GI nutritional shakes, have been demonstrated to improve post-prandial glucose levels ( 26 , 27 , 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to commonly used mid-meal snacks ( 13 , 42 ), pre-load represents a novel dietary approach to lower post-prandial glycemic excursions ( 14 , 43 ). A variety of foods, such as olive oil, milk proteins, fruits, and low-GI nutritional shakes, have been demonstrated to improve post-prandial glucose levels ( 26 , 27 , 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this study set out to determine the effect of a 3-month CR (without snacking between meals) on the anthropometric parameters, HOMA-IR index, and lipid profiles of 48 female office workers with BMIs exceeding the normal range by as much as 12%. The study participants were divided into 2 groups: one consisting of women who did not snack before the intervention, and the other group of women who had 1–5 healthy and unhealthy snacks per day, which increased their daily calorie intake [ 43 ] by ca. 110 kcal more compared with the NS group and triggered an extra release of insulin inhibiting fatty acid oxidation and fat tissue reduction [ 13 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that reducing body mass by means of a restricted calorie intake raises insulin sensitivity, protects pancreatic beta cells, and prevents the pro-the other group of women who had 1-5 healthy and unhealthy snacks per day, which increased their daily calorie intake [43] by ca. 110 kcal more compared with the NS group and triggered an extra release of insulin inhibiting fatty acid oxidation and fat tissue reduction [13,44].…”
Section: Changes Following Calorie Restrictionmentioning
confidence: 99%
“…The initial treatment of GDM involves diet modification, glucose monitoring, and moderate exercise. These findings highlight that medical nutritional therapy is the basis of GDM treatment (Persson et al, 2015) and is defined as the process of planning eating patterns, adapting the eating patterns and assessing the success of dietary interventions (Schübert et al, 2019). Persson Winkvist and Mogren (Persson et al, 2015) found that food plans should provide adequate calorie intake to improve fetal and maternal health, to acquire glycemic goals, and to increase weight according to gestational age.…”
Section: Management Of Gdmmentioning
confidence: 99%
“…Meals is defined as three main eating occasions "breakfast, lunch and dinner". Some women consume snacks as recommendations from healthcare professionals, their own preferences due to hunger/appetite or out of habit (Schübert et al, 2019).…”
Section: Management Of Gdmmentioning
confidence: 99%